Toward Efficient Wound Management: Bioinspired Microfluidic and Microneedle Patch (Small 3/2023). Issue 3 (18th January 2023) - Wang, Yuqiu; Gao, Bingbing; He, Bingfang
Abstract : Bioinspired Origami Microfluidic and Microneedle Patch Inspired by the highly folded structure of insect wings, a three‐dimensional (3D) origami microneedle (MN) patch with superfine miniature needle structures, microfluidic channels and multiple functions is reported to detect biomarkers, release drugs controllably and monitor motions to facilitate wound healing. More details can be found in article number 2206270 by Bingbing Gao and co‐workers.